ON THE QUESTION OF REMEDIES AVAILABLE TO THE EMPLOYEE IN CASE OF UNLAWFUL DISMISSAL - Вавженчук , Сергій; Гришина , Юлія; Мидель , Андрій (Київський національний університет імені Тараса Шевченка, 2022)
The article, on the basis of scientific doctrine, legislation of Ukraine, as well as judicial practice, examines certain issues related to the protection of an employee from wrongful dismissal in Ukraine, particularly, regarding the peculiarities of the application of such a remedy as reinstatement in the Ukrainian legal order. The authors emphasize the existence of a functional connection between the right to work, enshrined in the Constitution of Ukraine, and the employee's right to apply for protection in case of a wrongful dismissal by the employer. The article indicates the means of protection that can theoretically be applied by an employee who has been dismissed in violation of the requirements of the law. It is noted that reinstatement, based on the provisions of the legislation of Ukraine, can be considered the leading remedy available to the employee in case of a wrongful dismissal. At the same time, the authors note that the Labor Code of Ukraine does not provide the employee with an opportunity to choose a remedy that would reflect the needs of the particular employee in the most sufficient way. The article also attempts to explain the legal nature of reinstatement from the point of view of legal facts theory. In addition, the authors note that the proposed approach to the analysis of reinstatement allows explaining the compensation of average earnings for the period when the employee did not work because of the wrongful dismissal. This compensation can be interpreted as a natural consequence of reinstatement. At the same time, attention is focused on certain aspects of the relationship between the reinstatement of the employee and the payment to the employee of average earnings during the period of forced absenteeism. The article also describes the attitude of certain international organizations to reinstatement in the context of assessing the level of protection of employees under certain jurisdiction.

На основі наукової доктрини, законодавства України, а також судової практики досліджено окремі питання, пов'язані із захистом працівника від неправомірного звільнення в Україні, зокрема стосовно особливостей застосування у вітчизняному правопорядку такого засобу захисту, як поновлення на роботі. Підкреслено функціональний зв'язок між правом на працю, що закріплене в Конституції України, та правом працівника звернутись по захист у разі неправомірного звільнення роботодавцем. Наведено засоби захисту, які теоретично може застосувати працівник, якого було звільнено з порушенням вимог законодавства. Відзначено, що поновлення на роботі, виходячи з положень законодавства України, можна вважати провідним засобом захисту працівника від неправомірного звільнення. Водночас зазначено, що Кодекс законів про працю України не надає працівнику можливості вибору засобу захисту, який якнайкраще відображав би потреби конкретного працівника. Також здійснено спробу обґрунтувати та пояснити правову природу поновлення на роботі з погляду теорії юридичних фактів. Крім того, зазначено, що запропонований підхід до аналізу поновлення на роботі дозволяє обґрунтувати виплату середнього заробітку за час вимушеного прогулу як закономірного наслідку поновлення на роботі. При цьому акцентовано увагу на окремих аспектах співвідношення поновлення працівника на роботі та виплати працівнику середнього заробітку за час вимушеного прогулу. Також описано ставлення окремих міжнародних організацій до поновлення на роботі в контексті оцінювання рівня захищеності працівників у певній державі.
ДО ПИТАННЯ РОЗУМІННЯ ЗАСОБІВ ЗАХИСТУ ПРАВ ПРАЦІВНИКА ВІД НЕПРАВОМІРНОГО ЗВІЛЬНЕННЯ
Keywords: захист трудових прав; засіб захисту трудових прав; поновлення на роботі; неправомірне звільнення; розірвання трудового договору; protection of labor rights; employment remedies; reinstatement; wrongful dismissal; termination of the employment contract